The Gospel according to Saint Matthew in Anglo-Saxon and Northumbrian versions synoptically arranged, with collations of the best manuscripts - Kemble, John Mitchell ([Cambridge, The University Press, 1858)
iv, 231 p. 29 cm; "Designed and partly executed by John M. Kemble."; Preface signed: Charles Hardwick
Keywords: English language -- Old English, ca. 450-1100 Dialects